2017
DOI: 10.3233/jnd-170230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Azithromycin Monohydrate as a Single or a Combinatorial Therapy in a Mouse Model of Severe Spinal Muscular Atrophy

Abstract: It is important to explore various approaches for SMA therapeutics, hence compounds that specifically induce SMNΔ7 read-through, without having prohibitive toxicity, may provide an alternative platform for a combinatorial treatment. Here we established that AZM activity at a low dose can increase SMN protein in disease-relevant animal model and can impact disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This approach was very effective in a mouse model of SMA, and extended survival, improved weight gain and "time to right". Dr. Lorson also discussed combinatorial treatments for SMA, including SMN-dependent [15] and SMNindependent [16] approaches. Dr. Charlotte Sumner (Johns Hopkins University School of Medicine, USA) gave an overview of the genetics of SMA and the very promising therapeutics currently approved (Nusinersen/Spinraza) or in development (AVSX-101, scAAV9-SMN1).…”
Section: Session 1: Innovations In Neuromuscular Disease and Transformentioning
confidence: 99%
“…This approach was very effective in a mouse model of SMA, and extended survival, improved weight gain and "time to right". Dr. Lorson also discussed combinatorial treatments for SMA, including SMN-dependent [15] and SMNindependent [16] approaches. Dr. Charlotte Sumner (Johns Hopkins University School of Medicine, USA) gave an overview of the genetics of SMA and the very promising therapeutics currently approved (Nusinersen/Spinraza) or in development (AVSX-101, scAAV9-SMN1).…”
Section: Session 1: Innovations In Neuromuscular Disease and Transformentioning
confidence: 99%
“…The severity of SMA has so far indicated that there is a relatively short therapeutic window to achieve a maximal effect, however, adjunctive or combinatorial strategies may expand this window, thereby increasing the number and the types of patients that respond to drugs. (26)(27)(28)(29)(48)(49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment of a severe SMA mouse model with Azithromycin, an FDA approved readthrough drug, in combination with a sub-optimal ASO dose significantly improved disease phenotype over either treatment alone (29). An important pipeline for complementary therapeutic pathways revolves around the identification of potent disease modifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebroventricular (ICV) injections were performed at P2 as previously described 81,82 . For motor function analysis, time to right (TTR) experiments were conducted as previously described 38,83 . TTR was measured every day from P7 through P17 on control and SMNΔ7 experimental animal cohorts.…”
Section: Methodsmentioning
confidence: 99%